Analysis of serious games for preventing internet gaming addiction. (2018) - Kim, Ji Yun; Bae, Jae Hwan
Internet addiction and internet gaming (game) addiction are two terms regularly used in our daily lives, however, their distinction is rather vague. Internet gaming addition refers to a psychological, emotional, and social state where one, due to increased tolerance and dependence to games and other reasons, loses control over and plays internet games excessively and compulsively, and any efforts to reduce or stop playing will be ensued by withdrawal symptoms. One means to better the problems caused by gaming addiction is development of a variety of serious games and related services. Whereas internet games are played for entertainment, serious games utilise the entertainment function to further education and addition preventive measures objectives.